Association of Early Life Exposure to Phthalates With Obesity and Cardiometabolic Traits in Childhood: Sex Specific Associations - Vafeiadi, Marina; Myridakis, Antonis; Roumeliotaki, Theano; Margetaki, Katerina; Chalkiadaki, Georgia; Dermitzaki, Eirini; Venihaki, Maria; Sarri, Katerina; Vassilaki, Maria; Leventakou, Vasiliki; Stephanou, Euripides G.; Kogevinas, Manolis; et al. (Frontiers in Public Health, 2018)
Few studies have investigated longitudinal associations between early life phthalate exposure and subsequent obesity and cardiovascular risks in children with inconsistent results. We evaluated the associations between early life phthalate exposure with offspring obesity and cardiometabolic risk factors in 500 mother-child pairs from the RHEA pregnancy cohort in Crete, Greece. Seven phthalate metabolites [monoethyl phthalate (MEP), mono-n-butyl phthalate (MnBP), mono-isobutyl phthalate (MiBP), monobenzyl phthalate (MBzP), mono(2-ethylhexyl) phthalate (MEHP), mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), and mono(2-ethyl-5-oxohexyl) phthalate (MEOHP)] were quantified in spot urine samples collected from mothers (1st trimester) and their children at 4 years of age. We calculated the molar sum of DEHP metabolites (MEHP, MEHHP, MEOHP). We measured child weight, height, waist circumference, skinfold thicknesses, blood pressure (BP) and lipids at 4 and 6 years and leptin, adiponectin and C-reactive protein at 4 years. We used generalized estimating equations to examine associations at each age and tested for interaction by sex. Child exposure to phthalate metabolites was associated with lower BMI z-scores in boys and higher BMI z-scores in girls. Each 10 fold increase in ΣDEHP was associated with a change in waist circumference of -2.6 cm (95% CI: -4.72, -0.48) in boys versus 2.14 cm (95% CI: -0.14, 4.43) in girls (p-sex interaction= 0.003) and a change in waist-to-height ratio of -0.01 (95% CI: -0.03, 0.01) in boys versus 0.02 (95% CI: 0.01, 0.04) in girls (p-sex interaction= 0.006). Phthalate metabolite concentrations at age 4 were negatively associated with systolic and diastolic blood pressure. MEP was associated with lower systolic BP z-scores (adj. β= -0.22; 95% CI: -0.36, -0.08) at 4 years. MnBP and MBzP were associated with lower diastolic BP z-scores (adj. β= -0.13; 95%CI: -0.23, -0.04 and adj. β= -0.11; 95% CI: -0.21, -0.01, respectively). A 10 fold increase in MiBP was associated with 4.4 % higher total cholesterol levels (95% CI: 0.2, 8.7). Prenatal phthalate exposure was not consistently associated with child adiposity and cardiometabolic measures. Our findings suggest that early life phthalate exposure may affect child growth and adiposity in a sex-specific manner and depends on the timing of exposure.